Pengembangan Sistem Informasi Kredit Rumah Pegawai Pada Balai Pengelolaan Das Agam Kuantan Padang - Yulia Jihan sy; Rahmi Putri Kurnia; Novi Novi (UIN Imam Bonjol Padang, 2023)
After conducting directly research into the Balai Pengelolaan DAS Kuantan Agam to find out the problems being faced by observations and interviews (interviews) with interested parties, it was found that data in the processing of home loan system was still manually. Processing data uses Microsoft Office Excel by input data to the tables and using formulas in Excel. This is find the problems about processing data. The problem that find double data in the management data. The information have a long time for processing data. The solve for this problem is development of housing credit data management. Development is make a program that uses a database to data storage and data processing to quickly and precisely. So the report will be faster, precise and accurate. For running this system have a very adequate device. The methodology in this research is field research, library research and laboratory research.